MODERNIZATION OF THE STATE CUSTOMS SERVICE OF UKRAINE’S OPERATIONS IN THE CONTEXT OF EUROPEAN INTEGRATION: CHALLENGES AND PROSPECTS - Prokopenko, Valeriia; Melnyk, Olena; Doroshenko, Hanna; Chuzhdanova, Mariia (Український економічний часопис, 2024)
The article examines the modernization process of the State Customs Service of Ukraine in the context of European integration. The authors analyze the current challenges faced by Ukrainian customs, particularly those arising from the full-scale invasion by the russian federation. Key aspects of the European Union's customs system are discussed, including the EU Customs Code, Customs Risk Management System, Authorized Economic Operator program, and the New Computerized Transit System. Based on the EU's experience, the authors outline prospects and provide recommendations for improving Ukraine's customs system, taking into account its unique challenges and aspirations for European integration. The study emphasizes the importance of modernizing the customs service to accelerate Ukraine's integration into the EU.